Fertilization Efficiency Improvement On Nurseries Palm Oil Through The Use Of Oil Palm Plantation Waste - Pauliz Budi Hastuti; Sri Manu Rohmiyati (Jurnal Agrivet, 2016)
This experiment was carried out to determine the efficiency of inorganic fertilizer in the main nursery of oil palm with the application of empty fruit bunches and the addition of local microorganisms (MOL) Mucuna bracteata. The experiment was conducted by using a factorial design, arranged in a completely randomized design with three replications. The first factor was the dose of inorganic fertilizer (100%, 75%, 50%, 25% ), the second factors was dose of empty fruit bunhes (efb) compost (0%, 15%, 30%, 45% by volume), and the third factor was concentration of local microorganisms (MOL) M. bracteata (no,5%,10%). The results showed that the application of 25% inorganic fertilizer in the main nursery provide of oil palm seedling growth equal to 100% inorganic fertilizers. The application of 15% oil palm empty fruit bunches compost in the main nursery of regosol soil can replace inorganic fertilizer. Granting MOL Mucuna bracteata with a concentration of 5% to 10% have not been able to increase the growth of oil palm seedlings in the main nursery. Granting of oil palm empty fruit bunches can increase inorganic fertilization efficiency in the main nursery of oil palm.Keywords: fertilizer, efb, MOL, oil palm seedlings, main nursery